The effect of different microbial preparations on some soil characteristics - Jakab, Anita; Kátai, János (Acta Agraria Debreceniensis, 2012)
In pot experiment the effect of different microbial inoculants and their combinations with NPK fertilizer and wheat straw on some soil properties (physical, chemical, and microbiological parameters) were studied. The experiment was set up in 2011 at the Institute of Agricultural Chemistry and Soil Science, in a three replications, in a random block design. The studied soil type was calcareous chernozem soil from Debrecen (Látókép) with ryegrass (Lolium perenne, L.) test plant.At the end of the experiment in our laboratory the nitrate-nitrogen content of soil, the AL-soluble phosphorus and potassium content of soil, the urease enzyme activity of soil, the total number of bacteria and the number of microscopical fungi were determined.The results of the study were the following:– The straw treatment and the straw + biofertilizer combinations influenced positively the nitrate content of soil.– The NPK fertilization and the straw+bacterial fertilizer combinations had significant positive effect on the AL-soluble phosphorus content of the soil.– The biofertilization and the straw+biofertilizer combinations stimulated the AL-soluble potassium content of soil occasionally.– The total number of bacteria was influenced by the NPK fertilization, the bacterial fertilization and the straw+bacterial fertilizer combinations significantly.– In case of the number of microscopic fungi caused in some cases significant changes the NPK+bacterial fertilizer and straw+bacterial fertilizer combinations.– The soil urease enzyme activity was increased in all cases strongly especially by the straw+bacterial preparation combinations.